Two times of Gesualdo Bufalino’s "Complete Works" (Prassi Ecdotiche della Modernità Letteraria, 2017)
The Complete Works of Gesualdo Bufalino were published in the collection «Classici Bompiani» by publisher Bompiani, in two volumes: the first one, published in 1997, edited by Maria Corti and with notes by Francesca Caputo, the second volume edited by Francesca Caputo. In this paper Caputo examines the three steps of this edition: the first is hidden writing, the second is public activity, and the third is the staging of the complete works edition.
Keywords: Gesualdo Bufalino; complete works; editorial choises; philology